Estudio de la capacidad ofiofaga y la resistencia de la zopilota (Clelia clelia, Colubridae) de Costa Rica a los venenos de serpiente - Cerdas Fallas, Luis (1982)
The resistance of the non-venomous snake Clelia clelia (Colubridae) to 13 venoms of both viperid and elapid snakes was tested. Specimens were subjected to natural bites by venomous snakes and were injected with measured amounts of venom. Local reactions, change of behavior, or death did not occur, indicating a high resistance of this species to all of the venoms tested.